RESPONSE OF BUPROPION IN COMBINATION OF COGNITIVE BEHAVIORAL THERAPY IN SMOKING CESSATION AMONG CARDIAC DISEASE PATIENTS. - Azhar Memon1 , Samreen Ali2 , Mashkoor Ansari3 , Shagufta Memon4 , Nehal Shaikh5 , Yasmeen Shaikh6 , Kashif Rasheed Shaikh7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: The purpose of the trial is to assess the efficacy and safety of using bupropion in conjunction with cognitive-behavioral therapy (CBT) to help individuals with cardiac illness quit smoking. METHODOLOGY: A total of 40 individuals were split into two groups for a randomized controlled experiment, with group A getting bupropion and cognitive behavioral therapy (CBT) and group B receiving a placebo and CBT. While participants in the control group got a placebo and the same number of CBT sessions, those in the treatment group received bupropion for 7–12 weeks. RESULTS: Analysis of the findings was based on tobacco craving index and complete blood count of participants performed at two different interval that were at baseline and after completion of 12 weeks of treatment protocol and the results had provided evidences that at baseline tobacco craving index of participants in group A at baseline for level of craving was 2.55±0.51 that was reduced to 1.15±0.58 and the frequency had fallen from 2.5±0.51 to 0.9±0.71 cigarettes daily. In group B the values of tobacco craving index for level of craving at baseline was 2.55±0.51 that went down to 1.75±0.71 and frequency of cigarettes per day reduced from 2.6±0.5 to 1.45±0.6 CONCLUSION: Overall, the study indicates that bupropion plus CBT may be helpful in helping individuals with cardiac illness quit smoking, but they were not shown to be superior to CBT alone. It may be necessary to do more research with a bigger sample size and a longer follow-up time to substantiate the combo therapy’s efficacy.